Construction of enzalutamide-resistant cell model of prostate cancer and preliminary screening of potential drug-resistant genes. Issue 15 (August 2021) - Feng, Tao; Wei, Dechao; Zhao, Jiahui; Li, Qiankun; Guo, Pengju; Yang, Xiaobing; Li, Mingchuan; Jiang, Yongguang; Luo, Yong
Among many factors of causing castration-resistant prostate cancer (CRPC) progression, a growing number of evidences have shown androgen receptors play a critical role. Therefore, blocking androgen receptor remains a therapeutic goal of CRPC. However, resistance to androgen receptor inhibitors, for example, enzalutamide, limits therapeutic efficacy for many patients. In this study, to develop an enzalutamide-resistant cell model for molecular mechanism investigation of enzalutamide-resistance, we continuously treated C4-2B cells with multiplied concentrations of enzalutamide. The IC50 of resistant cells was identified as 14.7705 µM, and the resistance index was calculated as 12.4. In addition, we verified the resistance of resistant cells through experiments in vivo and found the genes in androgen receptor signaling pathway (androgen receptor, Jagged1, Notch1) and those in androgen receptor alternative signaling pathways behaved the opposite. For some of the former, their mRNA and protein expression reduced markedly while for the latter, for example, CXCR7, AKT, STAT3, FOXP3, they rose dramatically in the expression level of protein and mRNA. More importantly, the tumor volume, tumor wet weight, PSA and VEGF secretion level, positive staining rate of Ki67 nuclei in resistant strain heterogeneous tumor treated with enzalutamide were significantly higher than those of maternal cell heterogeneous tumor treated with enzalutamide, whereas no obvious difference was detected between resistant strain heterogeneous tumor treated with enzalutamide and those of the resistant strain treated with reference drug. Finally, we identified 654 differentially expression genes and 2 compounds (atracurium besilate, methotrexates) associated with the amelioration of enzalutamide-resistance. Overall, we successfully established an enzalutamide-resistance cell model and screened out some resistance genes and candidate small molecule drugs.